The Little India Riot: Domestic and International Law Perspectives - CHEN, Siyuan (Institutional Knowledge at Singapore Management University, 2014)
A riot involving hundreds of foreign labourers broke out in Little India, Singapore, on 8 December 2013. Only the second riot to occur in more than 40 years in fairly tranquil Singapore, the damage was extensive as rioters destroyed police and emergency vehicles and even injured dozens of police and civil defence personnel. The authorities only needed a few days to complete the investigations and shortly after, some of the alleged rioters were arrested and charged, while some of them were repatriated. The swiftness of the entire process prompted harsh criticism from international and local human rights groups, who claimed that the authorities had not been accountable and transparent enough, particularly with regard to the labourers who were repatriated. Specifically, they alleged a lack of due process and arbitrariness in the repatriation. The Singapore government defended its position by maintaining that everything it did was in line with Singapore law and even international standards as well. This article considers the claims from both sides by examining all of the relevant laws and concludes that while international law in the context of repatriation does uphold the supremacy of state sovereignty to a rather large extent (or at least implicitly permits repatriation without judicial process), the seemingly innocuous issuance of stern warnings by the police in the aftermath of the riot may have unintended legal and practical ramifications, in that they effectively extract pleas of guilt without the proper adjudicatory process of the courts, rendering those affected de facto ex-criminals.